Medicinal plants of Nepal: Distribution pattern along an elevational gradient and effectiveness of existing protected areas for their conservation - Acharya, KP; Chaudhary, RP; Vetaas, OR (Banko Janakari, 2009)
This study explores patterns of medicinal plant species richness along an elevational gradient in Nepal and the effectiveness of existing protected areas for their conservation. We used published data on the distribution of medicinal plants. The number of medicinal plants and the number of protected areas present in each 100 m elevation band were collated by interpolation. We tested the number of protected areas and the number of species as the response variables against elevation as a predictor variable. To explain the relationship between the total medicinal plant richness and their different life forms with elevation and protected areas, we used generalized additive models (GAMs) and scatter plots. The elevational distribution of medicinal plants as a whole and disaggregated into different life forms revealed hump-shaped patterns. The maximum richness of medicinal plants was found at an elevation of 1100 m a.s.l. but the maximum numbers of protected areas were found at elevations between 3000-3500 m a.s.l. There was negative correlation between the altitudinal distribution of protected areas and medicinal plants in Nepal. This study suggests that the protected areas of Nepal were less concentrated where medicinal plants diversity was rich. Key words: Elevation gradient, generalized additive model, medicinal plants, species richness doi: 10.3126/banko.v19i1.2178 Banko Janakari, Vol. 19, No. 1, 16-22